Dalit theology in the twenty-first century : discordant voices, discerning pathways - Clarke, Sathianathan, Ed (Oxford University Press, 2010)
Contributed articles presented at a Kolkata Symposium on "Dalit Theology in the Twenty-first Century" held in January 2008 at Bishop's College, Kolkata.